Systemic mixed infection in a brown caiman (Caiman crocodilus fuscus) caused by Mycobacterium szulgai and M. chelonae: a case report - M. Slany; Z. Knotek; M. Skoric; Z. Knotkova; J. Svobodova; V. Mrlik; M. Moravkova; I. Pavlik (Veterinární Medicína, 2010)
A five-year old female brown caiman (Caiman crocodilus fuscus) was admitted to a veterinary clinic because of anorexia and lethargy. Chronic deterioration of the patient's condition together with the formation of slushy stools coloured from brown to red was observed during the previous eight weeks. Physical examination showed significant apathy and cachexia. Radiographic examinations of chest and abdomen revealed no pathological findings. Initial blood tests revealed decreased hematocrit and low levels of haemoglobin. Despite treatment with enrofloxacin and intensive supportive therapy with amino acids, vitamins and mineral matter, the animal died 14 days after admission to the clinic. Post mortem examination revealed splenomegaly with a total destruction of inner organ structure together with multiple granulomas in liver and lungs. Ziehl-Neelsen staining of tissue samples from liver, lungs and spleen revealed numerous acid-fast bacilli consistent with Mycobacterium spp. Identification of isolates was carried out using PCR restriction analysis (PRA) of the hsp65 gene and DNA sequencing of the 16S rRNA gene. Two different mycobacterial isolates obtained from separate samples of liver, lungs and spleen were identified as M. chelonae and M. szulgai. This is the first report of mixed infection caused by M. chelonae and M. szulgai in a reptile.